Global Shortage of Nurses Continues - Muhammad Kamil Che Hasan; Mohd Khairul Zul Hasymi Firdaus (Jurnal Keperawatan Padjadjaran, 2022)
Nurses play an important role in providing healthcare to individuals, families, and communities. One of the major challenges that global health systems face is a nursing workforce shortage. Various factors such as job dissatisfaction, intention to leave, and burnout are some of the predictors of nurse turnover. Another significant concern is whether the profession will be able to attract enough nurses to care for populations in the future. To ensure a healthy population, governments and health policymakers around the world must invest in nursing and healthcare and pay attention to the needs of health systems. To avoid a shortage among nurses, the government and relevant policymakers should pay highly on this issue as it may impact our future healthcare systems.